Pós-modernidade, Revista Movimento e a produção do conhecimento na educação física - Húngaro, Vitor (2012)
In this dissertation, we now present, we investigate the impact of post-modern formulations in the production of knowledge in physical education, to analyze both the production of 10 (ten) years of the magazine Movimento, edited and published by School of Physical Education (ESEF) linked to the Federal University of Rio Grande do Sul (UFRGS). To achieve the proposed objectives was necessary primarily a study of recent societal transformations that enabled the emergence of the postmodern critique, and soon after made explicit undertake a critique of postmodernity. In a second step we made a historical development of Physical Education in Brazil, with the inflection point of the 1980s. And finally, we had a dense critical analysis on the journal publications, which showed a significant influence of postmodernism in these productions